Enchanted objects : design, human desire, and the Internet of things - Rose, David, ....- (New York : Scribner, 2014)
We are now standing at the precipice of the next transformative development: the Internet of Things. Soon, connected technology will be embedded in hundreds of everyday objects we already use: our cars, wallets, watches, umbrellas, even our trash cans. These objects will respond to our needs, come to know us, and learn to think on our behalf. David Rose calls these devices--which are just beginning to creep into the marketplace--Enchanted Objects. Some believe the future will look like more of the same--more smartphones, tablets, screens embedded in every conceivable surface. Rose has a different vision: technology that atomizes, combining itself with the objects that make up the very fabric of daily living. Such technology will be woven into the background of our environment, enhancing human relationships and channeling desires for omniscience, long life, and creative expression. The enchanted objects of fairy tales and science fiction will enter real life. Groundbreaking, timely, and provocative, Enchanted Objects is a blueprint for a better future, where efficient solutions come hand in hand with technology that delights our senses.
Prologue: My nightmare -- Part I: Four futures. Terminal world : the domination of glass slabs ; Prosthetics : the new bionic you ; Animism : living with social robots ; Enchanting everyday objects -- Part II: Six human drives. The dialectic interplay: fiction and invention ; Drive #1: Omniscience: to know all ; Drive #2: Telepathy: human-to-human connections ; Drive #3: Safekeeping: protection from all harm ; Drive #4: Immortality: a long and quantified life ; Drive #5: Teleportation: friction-free travel ; Drive #6: Expression: the desire to create -- Part III: The design of enchantment. The extraordinary capability of human senses ; Technology sensors and enchanted bricolage ; The seven abilities of enchantment. Glanceability ; Gestureability ; Affordability ; Wearability ; Indestructibility ; Usability ; Loveability ; Five steps on the ladder of enchantment -- Part IV : Enchanted systems. Transformer homes ; Collaborative workplaces ; Human-centered cities ; Six future fantasies ; A metaphor and a macro trend.
Includes bibliographical references (pages 277-285) and index.
Keywords: Information technology -- Social aspects; Technological innovations -- Social aspects; Internet of things; Embedded Internet devices; Ubiquitous computing